Antenatal diagnosis of left atrial isomerism and heterotaxy syndrome in fetus with Meckel-Gruber syndrome - Seçil Kurtulmuş; Savaş Demirpençe; Deniz Can Öztekin; Altuğ Koç; Vedide Tavlı (KARE Publishing, 2014)
We aimed to present a fetus with Meckel-Gruber syndrome (MKS) who had left atrial isomerism, heterotaxy syndrome and complete heart block. A 26-year-old healthy female was referred to our clinic in the 23rd week of her pregnancy. The fetus had multiple systemic anomalies including fetal heart. Fetal echocardiography revealed a horizontal liver, left-sided stomach and vena cava interruption with azygos continuation. There was also an apical trabecular ventricular septal defect, aorta and pulmonary artery arising from the left ventricle, pulmonary artery hypoplasia, pulmonary valve stenosis and left atrial isomerism. The heart rate was 46/min, consistent with third-degree atrioventricular block. Multiple anomalies including occipital encephalocele, bilateral polycystic kidneys, cleft lip, cleft palate, and polydactyly were also detected in the obstetric ultrasonography. The pregnancy was terminated in the 23rd gestational week based on the consensus of perinatology council. The autopsy examination confirmed the diagnosis of MKS, left atrial isomerism and heterotaxy syndrome. Although some cardiac defects have been reported previously in MKS fetuses, here we expand the cardiac spectrum of anomalies associated with MKS to include left atrial isomerism and heterotaxy syndrome.